Psychological Flexibility as a Buffer against Caregiver Distress in Families with Psychosis - Jansen, Jens E.; Haahr, Ulrik H.; Lyse, Hanne-Grethe; Pedersen, Marlene B.; Trauelsen, Anne M.; Simonsen, Erik (Frontiers in Psychology, 2017)
Background: Research has shown that caregivers of persons with psychosis play an invaluable role in recovery, but unfortunately, often report high levels of distress. While cognitive models of caregiver distress have been well-supported, there is still limited knowledge of the psychological factors involved. Recent advances in cognitive behavioral therapy seem to converge on the importance of acceptance- and mindfulness based processes. Aim: To examine the impact of psychological flexibility on caregiver distress in the early phases of psychosis, while controlling for known predictors of caregiver distress. Method: Within a cross-sectional design, 101 caregivers of 38 persons with first-episode psychosis in a clinical epidemiological sample completed a series of self-report measures. Results: A linear mixed model analysis found that, after controlling for caregiver socio-demographic factors, service user symptoms, drug use and global functioning, psychological flexibility was a significant predictor of caregiver distress. Conclusion: Greater level of psychological flexibility in caregivers, seems to be related to lower levels of caregiver distress. This finding corresponds to studies within a broad range of emotional disorders. There may be important clinical implications in terms of facilitating the process of acceptance through interventions from the ‘third-wave’ or contextual cognitive behavioral therapies.